Pembudayaan Keusahawanan Islam: Implikasinya terhadap Pembangunan Ummah Sejagat - Ali, Nor Aini; Kamri, Nor 'Azzah; Sarif, Suhaili (Jurnal Usuluddin, 2003)
Entrepreneurship is a vital foundation to economic development of a country. This is parallel to Islamic religion which encourages Muslim to get involved in entrepreneurship. This article attempts to review the concept of Islamic entrepreneurship and its implications in nation development. The article concludes that education is the most effective mechanism in cultivating the culture of Islamic entrepreneurship among Muslims.